Evaluation of Drought Tolerance Ability in Wheat Genotypes Through Comprehensive Stress Indices - Vahid Sedghiyeh; Fariborz Shekari; Amin Abbasi; Naser Sabaghnia; Mozaffar Roustaii (Hayati Journal of Biosciences)
The objective was to assess a range of stress indices to discern wheat genotypes resilient to drought stress, so forty-nine genotypes underwent scrutiny in both drought stress in rainfed conditions and non-stress settings (with supplementary irrigation), employing a 7 × 7 lattice layout with two replicates across years 2019 and 2020. The evaluation incorporated twenty stress indices anchored in yield under water stress (YS) and potential (YP) circumstances. Primary analysis indicated that eight indices (RDI, YSI, YI, K2STI, MRP, REI, RR and SSPI) did not give any new information, so they were eliminated in further analysis. Genotypes G33 (4234 kg ha-1) and G9 (2227 kg ha-1) were the best genotypes based on YP in 2019 and 2020, respectively. A positive association was observed between ATI and YP and between YS with DI and K1STI in the year 2019, while in the second year, such positive associations were not seen. We found some wheat genotypes G6, G9, G10 and G11 demonstrated high performance in both potential and rainfed conditions across two years, showing yield higher than 1,800 and 2,700 kg ha-1 for YS and YP, respectively, across both years. These genotypes were detected as the most tolerant genotypes by mean-based indices (TOL, HM, GMP, and MP) as well as SSI and ATI indices, so it can be concluded that these indices are more useful than other indices for identifying the most tolerant as well as the high yielding genotypes.